Digital Media-Based Reproductive Health Education on Adolescent Girls' Attitudes Toward Anemia Prevention - Maylatita Zunianto; Reny Retnaningsih; Nila Widya Keswara (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Anemia is a major public health concern among adolescent girls in Indonesia, particularly due to increased iron requirements and menstrual blood loss. Digital health education may provide an accessible and engaging approach to promoting anemia prevention. This study aimed to determine the difference in adolescent girls’ attitudes toward anemia prevention before and after digital media-based reproductive health education at SMP Negeri 06 Singosari, Malang Regency. A pre-experimental one-group pretest–posttest design was conducted among 42 eighth-grade female students aged 12–15 years. Data were collected using a structured attitude questionnaire administered before and after a 30-minute educational video intervention. Data were analyzed using a paired-sample t-test with a significance level of 0.05. Before the intervention, 18 students (42.9%) demonstrated positive attitudes, while 24 (57.1%) demonstrated negative attitudes. After the intervention, the number of students with positive attitudes increased to 32 (76.2%), while those with negative attitudes decreased to 10 (23.8%). The mean attitude score increased from 38.95 at pretest to 44.74 at posttest, with a statistically significant difference between the two measurements (p < 0.001). Digital media-based reproductive health education was associated with a significant increase in adolescent girls’ attitudes toward anemia prevention. Digital educational media may therefore be a useful approach to support school-based health promotion and anemia prevention programs among adolescent girls.